Lysosome biogenesis in health and disease. Issue 5 (18th October 2018) - Bajaj, Lakshya; Lotfi, Parisa; Pal, Rituraj; Ronza, Alberto di; Sharma, Jaiprakash; Sardiello, Marco
Abstract: This review focuses on the pathways that regulate lysosome biogenesis and that are implicated in numerous degenerative storage diseases, including lysosomal storage disorders and late‐onset neurodegenerative diseases. Lysosomal proteins are synthesized in the endoplasmic reticulum and trafficked to the endolysosomal system through the secretory route. Several receptors have been characterized that execute post‐Golgi trafficking of lysosomal proteins. Some of them recognize their cargo proteins based on specific amino acid signatures, others based on a particular glycan modification that is exclusively found on lysosomal proteins. Nearly all receptors serving lysosome biogenesis are under the transcriptional control of transcription factor EB (TFEB), a master regulator of the lysosomal system. TFEB coordinates the expression of lysosomal hydrolases, lysosomal membrane proteins, and autophagy proteins in response to pathways sensing lysosomal stress and the nutritional conditions of the cell among other stimuli. TFEB is primed for activation in lysosomal storage disorders but surprisingly its function is impaired in some late‐onset neurodegenerative storage diseases like Alzheimer's and Parkinson's, because of specific detrimental interactions that limit TFEB expression or activation. Thus, disrupted TFEB function presumably plays a role in the pathogenesis of these diseases. Multiple studies in animal models of degenerative storage diseases have shown that exogenous expression of TFEB and pharmacological activation of endogenous TFEB attenuate disease phenotypes. These results highlight TFEB‐mediated enhancement of lysosomal biogenesis and function as a candidate strategy to counteract the progression of these diseases. This article is part of the Special Issue "Lysosomal Storage Disorders" . Abstract : This review discusses how the transcription factor EB (TFEB) is implicated in lysosomal biogenesis and degenerative storage diseases. TFEB coordinates the expression of proteins participating in the autophagy‐lysosome pathway, including lysosomal enzymes and their transporters. TFEB is primed for activation in lysosomal storage disorders because of lysosomal stress, but TFEB function is impaired in some late‐onset neurodegenerative storage diseases because of specific detrimental interactions that limit TFEB expression or activation. Increased expression or activation of TFEB results in the enhancement of the autophagy‐lysosome pathway and ameliorates disease phenotypes in models of lysosomal storage disorders and other degenerative storage diseases. This article is part of the Special Issue "Lysosomal Storage Disorders" .